(untitled) (Journal of Fiber Bioengineering and Informatics, 2020)
Line balancing problems are common in the various departments of the garment industry. Different kinds of line balancing algorithms have been applied, for many years, in the apparel industry to solve these problems. Many variables and constraints must be taken into account when designing a manufacturing facility, such as the assembly line balance. For this purpose, lots of data have been collected from actual production systems, as well as alternative ones, in order to find the best line balancing algorithm. Studying the factors affecting line balancing, to identify the bottlenecks and enhance production system performance, is of utmost importance. Garment manufacturing firms, particularly those working on a small-lot and order basis, must respond rapidly to changes in clothing styles. For flexibility and fast response, the line manger must be aware of the current situation in his production system, in order to process orders on time. Furthermore, in order to increase productivity, it is essential for line managers to be able to understand the behavior of the production system and to generate alternative systems. Thus, the simulation model approach, developed for the garment industries, enables predictability and helps to increase total productivity. The aim of this research is to simulate a production line producing several models at the same time, in order to find the maximum number of products in a product mix that can be manufactured, at high quality and without wasting time. Results show that it is possible to produce up to five different products simultaneously on the same line.